Analisis Kebutuhan Belajar sebagai Dasar Penerapan Metode Field Trip dan Minat Baca terhadap Keterampilan Menulis - Pasaribu, Dwi Maulidayanti; Ramadhan, Syahrul (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study aims to analyse the learning needs that must be met in the application of the field trip method and to explore the characteristics of students' reading interests and their influence on their skills in writing observation report texts (LHO). The research method used is qualitative with a descriptive approach, involving Indonesian language teachers and 30 seventh-grade students at SMP Negeri 1 Aek Nabara Barumun, Padang Lawas Regency, as respondents. Data was collected through interviews, questionnaires, and documentation. The results of the study indicate that the field trip method is effective in improving students' writing skills, but it requires thorough preparation, clear instructions, and guidance during and after the observation activity. Additionally, students' reading interests were found to have a positive correlation with the quality of their writing, where students with higher reading interests tend to have a richer vocabulary and more structured idea organisation skills. This study recommends that LHO writing instruction integrate field trip methods with efforts to enhance students' reading interest, thereby supporting the optimal development of writing skills.